A mixed-method investigation of youth football coaches´ behaviours at half-time - Raya-Castellano, P. E.; Reeves, M. J.; Cárdenas, D.; Fradua, L.; McRobert, A. P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction Invasion games involve limited opportunities to affect performance during competition. Half-time breaks have been suggested as appropriate occasions to intervene, with coaches` non-verbal expressions changing players` perceptions of first-half performance (Van Kleef et al., 2019). Moreover, coaches` verbal communication at game breaks have typically been analysed during time-outs, end of quarters, and half-times in combination or have been examined qualitatively (Avugos et al., 2018). Therefore, a mixed-method approach was employed to explore the verbal behaviours of youth-elite coaches and their underpinning knowledge exclusively during half-time talks.